27 CLINICAL AND GENOMIC CORRELATES OF NEUTROPHIL GRANULOCYTE-MACROPHAGE COLONY STIMULATING FACTOR SIGNALING IN PEDIATRIC CROHN DISEASE. (18th January 2018) - Denson, Lee A; Jurickova, Ingrid; Karns, Rebekah; Shaw, Kelly A; Cutler, David J; Okou, David; Dodd, Anne; Mondal, Kajari; Aronow, Bruce J; Haberman, Yael; Linn, Aaron; Price, Adam; et al.
Abstract: Background and Aims: Neutralizing Granulocyte-Macrophage Colony Stimulating Factor auto-antibodies (GMAb) suppress neutrophil extrinsic GM-CSF signaling and increase risk for stricturing behavior in Crohn's Disease (CD). We aimed to define clinical, genomic, and functional associations with neutrophil intrinsic GM-CSF signaling in pediatric-onset CD. Methods: Missense mutations in CSF2RA, CSF2RB, JAK2, STAT5A, and STAT5B were identified using whole exome sequencing (WES) in 543 pediatric Inflammatory Bowel Disease (IBD) patients. Neutrophil intrinsic GM-CSF signaling was defined using the GM-CSF induced STAT5 stimulation index (GMSI) in 180 pediatric IBD patients and 26 non-IBD controls. Reduced GM-CSF signaling (GMSI Lo) was defined as the 20th percentile within the control group. Variation in neutrophil phospho-protein abundance, bacterial killing, and the global pattern of gene expression with the GMSI was determined. Results: We validated 18 potentially damaging missense mutations in CSF2RA and CSF2RB. CSF2RA A17G carriage increased from 10% in those with intact neutrophil GMSI to 32% in those with low GMSI (p=0.02). The frequency of reduced Staph Aureus killing increased from 17% in in those with intact neutrophil GMSI to 35% in GMSI Lo neutrophils (p=0.043). CD neutrophils with low GMSI exhibited specific alterations in phospho-protein networks and genes regulating cytokine production, wound healing, and cell survival and proliferation. Stricturing behavior increased from 7% in CD patients with both low GMAb and intact GMSI to 64% in patients with both elevated GMAb and low GMSI (p<0.0001). Conclusions: Low normal neutrophil intrinsic GM-CSF signaling is associated with CSF2RA missense mutations, alterations in cellular phospho-protein and gene expression networks, and higher rates of disease complications in pediatric CD. These data may inform new therapeutic approaches including ex vivo priming of myeloid cells by GM-CSF.